Substratum as a Driver of Variation in Periphyton Chlorophyll and Productivity in Lakes - Vadeboncoeur, Yvonne (CORE Scholar, 2006)
Quantifying periphyton (attached algal) contributions to autotrophic production in lakes is confounded by properties of substratum that affect community biomass (as chlorophyll content) and productivity. We compared chlorophyll content and productivity of natural algal communities (phytoplankton, epipelon, epilithon, epixylon, and epiphyton) experiencing high (>10%) incident radiation in lakes in the US, Greenland, and Quebec, Canada. Chlorophyll content and productivity differed significantly among regions, but they also differed consistently among communities independent of region. Chlorophyll content of periphyton on hard substrata (rocks and wood) was positively related to water-column total P (TP), whereas chlorophyll content of algae on sediment (epipelon) and TP were not significantly related. Chlorophyll content was up to 100× higher on sediments than on hard substrata. Within regions, chlorophyll-specific primary productivity was highest for phytoplankton and lowest for epipelon. Periphyton on hard substrata and on macrophytes (epiphyton) had similar rates of chlorophyll-specific productivity that were intermediate to those of epipelon and phytoplankton. Area-specific productivity of epipelon was 5 to 10× higher than area-specific productivity of periphyton on hard substrata. This broad geographic comparison indicates that, in low to moderately productive lakes under high-light conditions, algal communities have predictable differences in area-specific and chlorophyll-specific productivity based on substratum. As such, chlorophyll alone is an inadequate predictor of the relative contributions of different algal communities to total primary production. Our results highlight the importance of the relative abundance and spatial distributions of substrata in determining the role of the littoral zones in nutrient and energy cycles in lakes.